Frictional Characterization Of Grey Cast Iron Train Brake Block Using A Reduced Scale Dynamometer - Utama, Bernardus Prasetya; Budiono, Herru Santoso; Surojo, Eko; Muhayat, Nurul (Mekanika: Majalah Ilmiah Mekanika, 2022)
The brake block is an essential component that slows down and stops the train. The safety of this transportation is very dependent on the reliability of this component. One of the essential features of the brake block material is the coefficient of friction. The coefficient of friction of the brake block material should fulfill the requirements. The coefficient of friction of a material is measured using a friction test. Many friction testing methods have been developed to study the characteristics of friction materials. In contrast to previous studies, in this study, the frictional characteristics of gray cast iron brake blocks were evaluated using a reduced scale dynamometer. The friction test is carried out by pressing the brake block specimen to the surface of the rotating wheel. The specimen size of the brake block and carriage wheels is reduced to ¼ of the original size. The friction test is carried out at a contact pressure of 0.15, 0.20, 0.25, and 0.30 MPa and the friction speeds of 3, 6, 9, and 12 m/s. This study indicates that the coefficient of friction of the gray cast iron brake block decreases with increasing sliding speed and contact pressure.